2013
DOI: 10.1002/jcp.24337
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐γ promotes vascular remodeling in human microvascular endothelial cells by upregulating endothelin (ET)‐1 and transforming growth factor (TGF) β2

Abstract: Systemic sclerosis (SSc) is a complex disease characterized by vascular alterations, activation of the immune system and tissue fibrosis. Previous studies have implicated activation of the interferon pathways in the pathogenesis of SSc. The goal of this study was to determine whether interferon type I and/or type II could play a pathogenic role in SSc vasculopathy. Human dermal microvascular endothelial cells (HDMVECs) and fibroblasts were obtained from foreskins of healthy newborns. The RT Profiler PCR Array … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 47 publications
4
68
0
Order By: Relevance
“…The increased renovascular fibrosis caused by CSA is consistent with reported studies, which related CSA hypertension to vascular structural derangements including perivascular fibrosis (Lassila et al, 2001;Rezzani et al, 2005). Pertinent observations include the following: (i) reported studies including ours showed that enhanced ET/ transforming growth factor-beta1 (TGF-β1) signaling mediates tissue fibrosis caused by CSA (Chatziantoniou and Dussaule, 2000;El-Gowelli et al, 2014), (ii) ET B receptors reduce TGF-β1 and subsequently attenuate hypertension and renal failure progression in uremic animals (Lavoie et al, 2005), (iii) the ET/ET A receptor signaling promotes the TGF-β1-induced renal fibrosis (Chrobak et al, 2013), and (iv) celecoxib prevents and reverses liver fibrosis induced by carbon tetrachloride via decreasing TGF-β1 expression (Chávez et al, 2010). That said, it is plausible to suggest that the renovascular antifibrotic effect of celecoxib, triggered possibly by the increased ET B and decreased ET A receptor expression, contributed to the BP lowering effect of celecoxib in CSA-treated rats.…”
Section: Discussionmentioning
confidence: 87%
“…The increased renovascular fibrosis caused by CSA is consistent with reported studies, which related CSA hypertension to vascular structural derangements including perivascular fibrosis (Lassila et al, 2001;Rezzani et al, 2005). Pertinent observations include the following: (i) reported studies including ours showed that enhanced ET/ transforming growth factor-beta1 (TGF-β1) signaling mediates tissue fibrosis caused by CSA (Chatziantoniou and Dussaule, 2000;El-Gowelli et al, 2014), (ii) ET B receptors reduce TGF-β1 and subsequently attenuate hypertension and renal failure progression in uremic animals (Lavoie et al, 2005), (iii) the ET/ET A receptor signaling promotes the TGF-β1-induced renal fibrosis (Chrobak et al, 2013), and (iv) celecoxib prevents and reverses liver fibrosis induced by carbon tetrachloride via decreasing TGF-β1 expression (Chávez et al, 2010). That said, it is plausible to suggest that the renovascular antifibrotic effect of celecoxib, triggered possibly by the increased ET B and decreased ET A receptor expression, contributed to the BP lowering effect of celecoxib in CSA-treated rats.…”
Section: Discussionmentioning
confidence: 87%
“…On the other hand, interferon-␣ and interferon-␥ suppress mRNA levels of FLI1 gene in dermal microvascular endothelial cells and lipopolysaccharide stimulation reduces mRNA expression of FLI1 gene in macrophages (Chrobak et al, 2013;Ho and Ivashkiv, 2010). Thus, Fli1 expression is regulated at transcriptional and/or posttranslational levels in cell type-and context-dependent manners.…”
Section: Bosentan Reverses the Expression Of Fli1 By Increasing Its Pmentioning
confidence: 93%
“…Numerous immune molecules were elevated in the circulation but without elevation in corresponding skin mRNA, including IL-16, IL-18, and CD40 ligand. PAI1 is a product of inflamed endothelial cells (120), that could be induced by cytokines increased in the blood. Leptin, the hormone associated with obesity, was 1.5 log 2 (FCH) times higher in psoriasis patients versus healthy volunteers, and higher in psoriasis patients with BMI >30 (mean 24 ng/ml) versus psoriasis patients with BMI <30 (mean 7 ng/ml) (119).…”
Section: Comorbidities In Psoriasismentioning
confidence: 99%